Contemporary art in the Federal Republic of Germany: 12 collections of 30 graphics : graphic art from Kunstvereinen. - Herzogenrath, Wulf (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1975)
Albrecht, Joachim ; Altrock, Hartmut von ; Badura, Michael ; Bremer, Uwe ; Breuer, Léo ; Deventer, Friedel ; Fruhtrunk, Günter ; Girke, Raimund ; Hajek, Otto Herbert ; Kallhardt, Rainer ; Leissler, Arnold ; Lenk, Kaspar Thomas ; Neuenhausen, Siegfried ; Ott, Manfred ; Winner, Gerd ; Pfahler, Georg Karl ; Piene, Otto ; Richter, Gerhard ; Roth, Dieter ; Sandig, Armin ; Sauer, Michel ; Schröder, Wolfgang ; Schwering, Bernd ; Sorge, Peter ; Staeck, Klaus ; Störtenbecker, Nikolaus ; Trökes, Heinz ; Vennekamp, Johannes ; Wewerka, Stefan ; Wilding, Ludwig
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland